Pengaruh Literasi Digital, Karakter Kewirausahaan dan Keunggulan Bersaing Terhadap Keberhasilan Berwirausaha - Saragih, Nara Pangihutan; Annisa, Najibah; Simamora, Dea Riskyalina; Munte, Gey Des Four; Umar, Andi Taufiq (FEB Universitas Maritim Semarang, 2025)
This study centers on examining the impact of digital literacy, entrepreneurial characteristics, and competitive advantage on entrepreneurial success. In the rapidly evolving digital era, the ability to utilize information technology has grown to be a crucial aspect in supporting business activities, specifically for micro, small, and medium enterprises (MSMEs). This analysis employs a quantitative method using surveys aimed at MSME entrepreneurs. Multiple linear regression was conducted to analyze the relationship between independent variables and the dependent variable. The outcomes reveal that digital literacy, entrepreneurial characteristics, and competitive advantage have a positive and significant effect on entrepreneurial success. These findings suggest that enhancing digital literacy, entrepreneurial attitudes and behaviors, and strategies to build competitive advantage are key factors in achieving business success.